Community mental health funding, stakeholder engagement and outcomes: a realist synthesis - Walter P Wodchis; Vicky Stergiopoulos; Katie N Dainty; Maritt Kirst; Andrea Duncan (BMJ Open)
Objectives This study sought to understand how stakeholder engagement impacts outcomes when there is a change in public funding within community mental health settings.Design A realist synthesis approach was used to address the research question to fully understand the role of stakeholder engagement as a mechanism in achieving outcomes (system and service user) in the context of community mental health service reform. An iterative process was used to identify programme theories and context–mechanism–outcome configurations within the literature.Results Findings highlight that in the absence of stakeholder engagement, funding changes may lead to negative outcomes. When stakeholders were engaged in some form, funding changes were more often associated with positive outcomes. Stakeholder engagement is multifaceted and requires considerable time and investment to support achieving intended outcomes when funding changes are implemented.Conclusions To support successful transformation of community mental health programmes, it is important that stakeholders are meaningfully engaged during funding allocation changes. Stakeholder engagement may entail connecting around a shared purpose, individual participation and meaningful interactions and dialogue.